Cherub : Mission 2 : The Dealer - Muchamore, Robert (New York Simon Pulse, 2010)
James embarks on a dangerous mission for the CHERUB agency, taking down the world's most powerful drug lord, putting his own safety aside in the hopes of ridding the streets of dangerous drugs.
Keywords: Spy stories -- Drug traffic -- Orphans